Rheumatoid neutrophilic dermatitis - Biagio Scotti; Cosimo Misciali; Yuri Merli; Federico Bardazzi; Diego Abbenante; Emi Dika; Bianca M. Piraccini (JEADV Clinical Practice)
Abstract Rheumatoid neutrophilic dermatitis (RND) is a dermatological condition typically associated with rheumatoid arthritis (RA). The low prevalence of RND and the wide spectrum of its possible clinical appearances make the diagnosis challenging. Current literature is still lacking a comprehensive overview of this rare cutaneous disorder. The aim of this review is to summarize data from the existing literature on RND, focusing on its epidemiology, clinical manifestations, histopathology and treatment. Hence, a comprehensive literature search of case reports and series was made, starting from a Medline (via PubMed) and Scopus databases. We also included in the analysis one patient attending to our dermatology department and diagnosed with RND. Overall, 54 cases of RND were identified. The majority of patients were female (72.3%) with a median (IQR) age at the time of diagnosis of 58 (65‐45) years. RND followed the onset of RA in 87% of patients with an average (SD) latency time of approximately 10 (8.9) years. In 1 (1.8%) case the dermatitis preceded the appearance of joint symptoms, while in three (5.5%) cases it occurred concomitantly with them. Seropositive RA was the major associated form (76.5%). Clinically, asymptomatic papules (31%), nodules (15.1%) and/or plaques (13.5%) distributed bilaterally on extremities were most frequently described. Notably, females were more prone to develop a painful dermatitis (84.6%) compared to males. The vesicobullous (12.7%) and pustular (9.2%) clinical subtypes were the most demonstrative in contrast to the urticarial skin manifestations and the potential figurative/annular distribution of the lesions. Spontaneous resolution of RND was rare (5.5%). Systemic treatments, mainly represented by steroids and anti‐neutrophilic agents (dapsone, colchicine), were consistently required.